Enhancing Students’ Interest in Agriculture Through the Integration of Ethnoecology in Biology Education - Yohanes Kamakaula; Obadja Andris Fenetiruma; Yunita Palinggi (International Journal of Educational Narratives, 2026)
Background. The integration of local knowledge in science education is considered an effective approach to bridging the gap between theoretical content and students’ real-life experiences. Ethnoecology, which examines the relationship between communities and their natural environment through culturally transmitted practices, provides a relevant framework for contextualizing biology learning, particularly in agrarian settings. Purpose. This study aims to examine how the integration of ethnoecology in biology education can enhance students’ interest in the agricultural sector. Method. A qualitative design was employed using a literature review and conceptual analysis. Data were collected from peer-reviewed journal articles, academic books, and prior studies related to ethnoecology, local wisdom-based learning, and biology education. The analysis was conducted through systematic source selection, conceptual categorization, and thematic interpretation. Results. The findings indicate that the ethnoecological approach improves students’ understanding of ecological concepts, increases the relevance of learning to everyday life, and promotes appreciation of local agricultural practices as both scientific knowledge and cultural heritage. Conclusion. The integration of ethnoecology into biology learning is an effective strategy for enhancing students’ interest in agriculture while supporting the preservation of local knowledge and the development of sustainable agricultural practices.